Bioadsorvente derivado da pachira aquatica aubl. no processo de biossorção para remoção de metais em efluentes - Nascimento, Talita Lorena da Silva do (2021)
The use of agro-industrial products to remove contaminants through the adsorption process has been a sustainable alternative due to its renewable origin, abundance, low cost and efficiency compared to commercial coal. In this sense, the present study aimed to investigate the use of a bioadsorbent derived from the fruit peel of aquatic Pachira for the removal of metallic ions in aqueous solution. The bioadsorbent was produced by carbonization of the biomass husks at 450 °C, and characterized through immediate analysis, XRD, SEM, the zero charge potential, zeta potential, thermogravimetry and Boehm titration. The full factorial design with central points was applied to optimize the adsorption tests and verify the influence of the concentration of Ni2+ and Cd2+ metallic ions, adsorbent mass and temperature on the removal capacity of such ions. The adsorption tests were developed using batch and fixed bed column systems. The kinetic tests indicated the occurrence of chemisorption, and the pseudo second order model was the one that best fit the experimental data. Process equilibrium was reached within 300 min with 81% and 96% removal for Ni2+ and Cd2+, respectively. The isothermal tests showed that the model that best described the process was the Langmuir model, also suggesting the occurrence of chemisorption, and that increasing the concentration of adsorbate increased the number of ions removed by CPA. The study of adsorption thermodynamics showed that the system, for both ions, is endothermic, since the ΔH values were positive, and that the adsorption conditions are non-spontaneous, indicated by the positive ΔG results. Furthermore, the results of ΔH >20 kJ/mol for both ions confirmed that the process occurred was that of chemisorption. The rupture curves showed that at a flow rate of 3 mL/min and bed height of 12 cm there were better removal results. The adsorption capacity of metals in the fixed bed column was greater for Cd2+ than Ni2+. It was observed that for adsorbate concentration of 100 mg/L, the break-up time was reached very quickly, however, by decreasing the concentration to 45 mg/L, this time was increased by about 6x. The bioadsorbent produced from the fruit peel of the Pachira aquática has the potential to remove metals in industrial effluents, providing sustainable valorization of a forest by-product through its application in effluent treatment systems.